PENINGKATAN EKONOMI PERTAHANAN NEGARA MELALUI IMPLEMENTASI NILAI-NILAI LUHUR DALAM LAGU POP DAERAH DI KABUPATEN MANGGARAI (KAJIAN IMPLIKATUR) - Elisabet Oktaviani Hanggu; Odilia Jayanti Mahu (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to describe the form of core values ​​contained in the implicature of the Manggarai regional popular song and to describe the meaning contained in these implicatures. This research was a qualitative descriptive study. The data collection technique was done by listening to and recording the lyrics that contained implicatures. The data analysis technique used was the equivalent method with the basic technique of sorting the determining elements. The research findings showed that, first that there were forms of core value range in Manggarai pop songs namely, (1) values ​​related to oneself including loyalty (2) values ​​related to society citizenship, compassion, and mutual cooperation (3) values related to nature includes devotion to nature and respect for natural health (4) values ​​related to God including being pious. The value purposes relating to society contained to giving an information and commanding.